2018
DOI: 10.1002/aqc.2993
|View full text |Cite
|
Sign up to set email alerts
|

A spatially explicit approach to prioritize protection areas for endangered freshwater mussels

Abstract: In spite of their conservation importance, only a fraction of lakes and streams globally – including their catchments – are currently covered by conservation areas. To identify conservation gaps, assessing the spatial distribution of biodiversity in relation to conservation areas is a promising approach. A gap‐analysis approach was used to evaluate the protection status of the habitats of two endangered freshwater mussel species, Margaritifera margaritifera (Linnaeus, 1758) and Unio crassus (Philipsson, 1788),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 67 publications
0
17
0
1
Order By: Relevance
“…Therefore, future studies should include predictors associated with host fishes, mussel dispersal, and other land‐use patterns, such as mining and dams that may influence mussel populations in the Amazon. Management plans should include areas for conservation in both buffer and subcatchment scales since these are important for freshwater mussel distribution (Dobler et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future studies should include predictors associated with host fishes, mussel dispersal, and other land‐use patterns, such as mining and dams that may influence mussel populations in the Amazon. Management plans should include areas for conservation in both buffer and subcatchment scales since these are important for freshwater mussel distribution (Dobler et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of suitable habitats for mussels is important for aquatic conservation because they may be found in a diverse array of habitats (Dobler et al., 2019 ; Smit & Kaeser, 2016 ). For example, mussels may occur in gravely or sandy river substrates (Allen & Vaughn, 2010 ; Steuer et al., 2008 ), whereas others may aggregate among large cobbles (Gangloff & Feminella, 2007 ) and similar flow refuges, which are sheltered and remain stable in periods of high flow (Morales et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the southeastern U.S. contains the greatest diversity of fish, reptiles, and amphibians, but disproportionately few protected areas (Jenkins et al 2015). Studies outside the U.S. have found mixed associations between freshwater protection and representation of freshwater biodiversity (Abraham and Kelkar 2012, Chessman 2013, Guareschi et al 2015, Dobler et al 2019. Therefore, protected areas may not only insufficiently protect freshwaters, but also the full breadth of freshwater ecosystems and biodiversity.…”
mentioning
confidence: 99%
“…Furthermore, the conservation of habitats of those species already protected may also gain from legislative measures. Dobler, Geist, Stoeckl, and Inoue () showed that designated sites such as the special areas of conservation (SACs) selected for mussel species in Bavaria are frequently too small to be effective, as in many cases the SACs do not cover the catchment areas of the streams. This means that critical factors such as nutrient and sediment loads originating from the wider catchment cannot be reduced using the legal instruments of the Habitats Directive.…”
Section: Discussionmentioning
confidence: 99%